(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to analyze Ahmed Shawqi’s poem elegizing Omar Al-Mukhtar in light of Text Linguistics, through applying Robert de Beaugrande’s textuality standards: cohesion, coherence, intentionality, acceptability, informativity, situationality, and intertextuality، The study adopts the descriptive analytical method to reveal the aspects of textual cohesion and coherence in the poem, and to clarify how the overall meaning is formed through linguistic, semantic, and contextual relations، The study concludes that the poem is not merely a traditional elegy, but rather a national and human poetic discourse that transforms Omar Al-Mukhtar’s martyrdom into a symbol of resistance, freedom, and immortality، The findings also show that the textuality standards are clearly achieved in the poem, giving it thematic unity as well as semantic and artistic cohesion.